Design a new energy absorber longitudinal member and compare with S-shaped design to enhance the energy absorption capability - Samer Fakhri Abdulqadir (Alexandria Engineering Journal, 2018)
A numerical investigation study of both direct and oblique crush loading was implemented. The study used ductile metallic alloy (mild steel A36) and magnesium alloy (AZ31). The study used hexagonal tube as longitudinal members. The current design consists of two parts, the inner tube which is the longitudinal and the outer is the supporting system which is the telescope. Aluminum foam incorporated to the design to enhance the crashworthiness performance. The design is subjected to impact speed of 54 km/h with the impact mass of 1100 kg using three different collision directions: direct, 40 per cent offset and oblique direction with 30 degrees.From the SEA results it can be concluded that the current design (made of steel) enhanced the specific energy absorption by 194% from the highest design used. While the current design made up of magnesium alloy increased the SEA by 255% from the best design which was foam filled s-shaped with square section. The decelerations of the current design for the three directions were at the low permit level which will put the compartment car at the low level of deformation during collision. Keywords: Energy absorption, Steel, Magnesium alloy, Direct impact, Oblique impact